Collaboration management framework for OEM – suppliers relationships: a trust-based conceptual approach. Issue 7 (9th August 2017) - Belkadi, Farouk; Messaadia, Mourad; Bernard, Alain; Baudry, David
ABSTRACT: Due to the increased competitiveness and the diversity of requirements in today's markets, manufacturing companies need to join their competencies and resources to propose innovative solutions for each specific market, with the possibility to transpose these solutions to another market, by means of slight adaptations. Thus, manufacturing firms must constantly conduct new collaborations with known partners in most cases, but also with new partners. The critical question for managers in this latter case is how to define the best collaborative strategy according to the goals of the project and the specificity of the target market. This paper tackles the problem by proposing a conceptual framework for supporting the management of collaborative situations in the case of Original equipment manufacturers (OEMs). Based on the concept of trust level, the framework proposes a classification of different collaboration modes to be adopted in various contexts of inter-enterprise relationships, in manufacturing sector. The aim is to support the flexible navigation between different collaborative situations by taking into account all decision-making levels from the strategy to the implementation of the information technologies (IT) systems at the operational level.